Optimization of processing conditions of starch-based hydrogels produced by high-pressure processing (HPP) using response surface methodology - Koshenaj, Katerina; Ferrari, Giovanna (Frontiers in Food Science and Technology, 2024)
This study aimed to determine the optimal processing conditions to produce stable starch-based hydrogels by high-pressure processing (HPP) viausing the response surface methodology. The experiments were carried out with different starch suspensions, namely rice, corn, wheat, and tapioca starch, at a concentration in the range of 10 -40 % w/w, processed at a pressure level of 600 MPa and holding times between 5 min and 15 min. The investigation was carried out using different starches, namely rice, corn, wheat, and tapioca starch solutions at a concentration in the range 10 -40 % w/w. The HPP processing conditions were a constant pressure of 600 MPa and holding times between 5 min and 15 min. Gel formation was assessed by determining the gelatinization extent and structuring level of the samples. The results demonstrated that starch/water ratio and holding time had a significant impact on gel formation in HPP treatments. Various degrees of gelatinization were observed in the treated samples due to the starch's water absorption capacity of the starch and the molecular interactions between water and starch occurring that occur during gelatinization. Moreover, a highly structured hydrogel formed at starch concentrations higher than 25% (w/w), whereas a low-structured hydrogel formed at concentrations lower than 20% (w/w) ,when starch concentration was less than 20% (w/w) lower-structured hydrogels formed, as confirmed by the values of the efficiency index measured. Completely gelatinized, highly structured, and stable HPP hydrogels were obtained from starch solutions treated at the optimized processing conditions. by the efficiency index. Samples treated under optimized conditions (rice starch concentration equal to 23.5% and processing time of 13 min; corn starch concentration equal to 23.9% and processing time of 13min; wheat starch concentration equal to 19.6% and a processing time of 11 min; tapioca starch concentration equal to 20% and a processing time of 15 min) were completely gelatinized and highly structured and stable starch based HPP hydrogels were obtained.